Teachers' Understanding of the Merdeka Curriculum: A Qualitative Study in a Rural Indonesian Elementary School - Moh Rifaldi; Sarintan N Kaharu; Pahriadi Pahriadi; Azizah Azizah; Sukri Sukri (Journal of Innovation and Research in Primary Education, 2026)
This study examined teachers' understanding of the Merdeka Curriculum at SDN 2 Dolo, focusing on conceptual comprehension and practical implementation of curriculum components. The curriculum emphasizes student-centered learning, differentiated instruction, and character development through the Pancasila Student Profile. Understanding teacher readiness is crucial for effective implementation, yet many Indonesian teachers struggle with both conceptual and procedural demands of curriculum reform. This qualitative descriptive study involved four classroom teachers selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, questionnaires, and documentation analysis over two months. The Miles et al. interactive model guided data analysis through reduction, display, and conclusion drawing. Findings revealed that teachers demonstrated strong philosophical alignment with curriculum principles but significant gaps in technical implementation skills. While all teachers embraced student-centered learning concepts, 75% reported difficulties in developing learning objective flows (ATP) and 100% acknowledged inadequate understanding of diagnostic assessment practices. Teachers relied heavily on government-provided materials rather than designing independent teaching modules. However, an unexpected finding showed high teacher motivation and willingness to improve despite these challenges. The study concludes that effective curriculum implementation requires professional development addressing both conceptual understanding and procedural competencies through sustained training, collaborative learning communities, and mentoring support. These findings contribute to understanding the dual nature of teacher knowledge in curriculum reform contexts.